A mixed methods evaluation of the Emotional Literacy Support Assistants (ELSA) project - Mann, David (2014)
This study aimed to contribute to the small evidence base on the Emotional Literacy Support Assistant (ELSA) project. The ELSA project is an Educational Psychologist led training programme for Teaching Assistants’ (TA) providing modular input combining background psychological theory with practical guidance to meet the emotional needs of pupils in the context of a school (Burton, 2008). Existing research (Burton, Osborne and Norgate, 2010) has demonstrated that the ELSA project has a significant impact on teaching assistants’ perceptions of pupil emotional literacy and behavioural adjustment. However, current evaluations are unable to demonstrate if these impacts are recognised by the pupils themselves. This research aimed to explore the perceptions of recently trained ELSAs regarding their role and training in supporting the development of emotional well-being. The study was also interested in exploring whether there the ELSA project has a measurable impact on pupils’ emotional well-being. A pragmatic, mixed methods design is discussed, first in terms of a pre-test – post-test non-equivalent groups design, quantitative method that included 5 TA and 5 pupil experimental group participants and 1 TA and 5 pupil comparison group participants. The Emotional Literacy Checklist (Faupel, 2003) and Strengths and Difficulties Questionnaire (Goodman, 1997) measured pre and post-test changes in teacher and pupil participant scores. Secondly qualitative methods included thematic analyses of focus group and questionnaire data gathered at different time points from the recently trained ELSAs. It was not possible to determine whether the ELSA project had an impact on pupils’ emotional well-being. However, thematic analyses suggested that participants perceived the ELSA training to be of value in terms of their personal and professional development and the support gained. There was also evidence to suggest that participants shared a perception that the perceptions of their colleagues regarding their role and time restraints were a primary challenge to their role. Professional implications of these findings and future research, in light of methodological limitations, are discussed.